Powerful conversations : how high impact leaders communicate - Harkins, Philip J. (McGraw Hill Education on BrillianceAudio., 2017)
Business communications expert Phil Harkins helps Fortune 500 companies drive growth and increase productivity with his proven strategies. Now, this edition of his communications classic offers the insight and expertise required to seize the competitive edge in your own industry. Packed with goal-oriented strategies, tools, and real-life examples from some of today's top leaders, Powerful conversations helps you advance both personal and organizational goals with every word you speak.